Grain structure and strength of a plastically deformed Ni3Al intermetallic compound - Ovcharenko V. E. Vladimir Efimovich; Boyagin E. N. Evgeny Nikolaevich; Myshlyaev M. M. Mikhail Mikhaylovich; Ivanov Yu. F. Yury Fedorovich; Ivanov K. V. Konstantin Viktorovich (Technical Physics, 2015)
Title screen